Plagiarism in Education Programmes Legitimised Dishonesty or Lack of Awareness? - Ramachandran, Hema; Sinha, Divya; Rajadhyaksha, Medha S. (JOURNAL OF INDIAN EDUCATION, 2017)
Data and literature available due to technological advancements in computation and internet connectivity has encouraged plagiarism among undergraduate and postgraduate students.We addressed the question whether this is because of lack of awareness about plagiarism and its serious consequences amongst students and teachers or whether plagiarism is permitted as a soft crime. We conducted a survey amongst students and teachers using the questionnaire method. The major questions were related to whether the student/faculty was informed about plagiarism, and whether they know that plagiarism is a serious misconduct. Questions also assessed whether the subjects recognised plagiarism and knew about ‘referencing’. On the basis of our study, we suggest that there is lack of awareness in students about the various aspects of plagiarism and there is a feeling in the academic community that plagiarism is somewhat permitted. We propose some ways to correct the situation and ensure development of skills for original writing.